Inclusão nas aulas de educação física: o conhecimento dos professores das escolas de Miracema do Tocantins - TO - Melo, Maria Marta Rodrigues de (Universidade Federal do Tocantins, 2021)
Physical Education is an area of knowledge that can to contribute with work aimed at inclusion of disabled students in regular education. This area explores the contents of the movement body culture (sports, dance, gymnastics, fights, games and playing) adapting and providing diverse experiences that guarantee the inclusion of all students. Thus, it is important to know the characteristics of the individual so that mistakes are avoided in the inclusion process. With this, the aim of research was to verify the knowledge perception of teachers on subjects necessary for to act and to include students with disabilities in the classes of Physical Education in the regular education. Was realized a field research in the network municipal teaching of Miracema do Tocantins with the participation of 10 Physical Education teachers, their filled a questionnaire with 14 questions on the teacher's knowledge regarding disabled students. The results show that although the majority of teachers indicated a regular or good knowledge (25% + 42% = 67%) on the subjects related to the inclusion of people with disabilities, many of them, by justifying and exemplifying their knowledge, gave answers inadequate or inconsistent with the knowledge attributed. It observe a contradiction between the knowing and doing in the professional practice of the teachers who participated in the research. It Indicate the implementation of professional training and qualification policies in the municipality, mainly, to work with disabled children and young people. Future research is suggested that can identify the conditions, pedagogical resources and structural to make adaptations and accessibility in schools of the city.